2022
DOI: 10.5001/omj.2022.98
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome and Risk Assessment in Hospitalized COVID-19 Patients with Elevated Transaminases and Acute Kidney Injury: A Single Center Study

Abstract: Objectives: Initial reports indicate a high incidence of abnormal aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels in patients with COVID-19 and possible association with acute kidney injury (AKI). We aimed to investigate clinical features of elevated transaminases on admission, its association with AKI, and outcomes in patients with COVID-19. Methods: A retrospective analysis of the registered data of hospitalized patients with laboratory-confirmed COVID-19 and assessment of the AST … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Potential contributing factors may encompass ischemic damage, damage induced by systemic inflammation akin to sepsis, and coagulation abnormalities involving both microvascular and macrovascular thrombosis. 38 The kidneys are susceptible to damage during COVID-19 infection, leading to acute kidney injury (AKI). This study observed a 23.3% incidence of increased creatinine among patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Potential contributing factors may encompass ischemic damage, damage induced by systemic inflammation akin to sepsis, and coagulation abnormalities involving both microvascular and macrovascular thrombosis. 38 The kidneys are susceptible to damage during COVID-19 infection, leading to acute kidney injury (AKI). This study observed a 23.3% incidence of increased creatinine among patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in those patients requiring ICU support, AKI is associated with poor prognosis and increased risk of mortality. As a result of the studies mentioned above, we have observed that many laboratory parameters are useful as potential biomarkers to predict renal damage associated with COVID-19 [ 15 , 17 , 21 , 22 , 23 , 24 , 27 , 30 , 48 , 49 , 50 ].…”
Section: Methods: Identification and Characteristics Of Included Studiesmentioning
confidence: 99%